Anti-aging properties of Curcuma heyneana Valeton & Zipj: A scientific approach to its use in Javanese tradition. (28th October 2018) - Kusumawati, Idha; Kurniawan, Kresma Oky; Rullyansyah, Subhan; Prijo, Tri Anggono; Widyowati, Retno; Ekowati, Juni; Hestianah, Eka Pramyrtha; Maat, Suprapto; Matsunami, Katsuyoshi
Abstract: Ethnopharmacological relevance: Temu giring, the rhizome of Curcuma heyneana Valeton & Zipj ( C. heyneana ), is native to tropical regions, especially in Indonesia. It is traditionally used as a skin care, for cosmetic and body freshness, in Javanese and Balinese women, and has many other bioactivities such as antioxidant, anticancer and antiinflammatory. Aim of the study: The purpose of this study was to determine the antiaging activity of C. heyneana to prove its traditional use. Materials and methods: The antioxidant activity was determined using the DPPH free radical method, and anti-aging activity was examined using in vitro assays such as tyrosinase inhibitor and collagenase inhibitor. In vivo tests were performed by observing histomorphologic changes in rat skin exposed to Ultraviolet (UV) rays. The total curcuminoid contents and chromatographic profiles were determined by Thin Layer Chromatography (TLC) – densitometry. Results: In all in vitro assays, all of the extracts showed a dose-dependent manner in the final concentration range from 62.5 to 500 µg/mL for DPPH assay and 31.25 to 250 µg/mL for tyrosinase inhibition and collagenase inhibition assay. Curcuminoid (CUR), the active principle of Curcuma genus shows antioxidant, tyrosinase inhibitor and collagenase inhibitor activity greater than all C. heyneana extracts. The in vivo assay results showed that the topical application of the crude extract of C. heyneana produced significant improvement effects on the UV-induced skin structure damage. The total CUR content was correlated with the anti-aging activity of Curcuma heyneana . Conclusions: The results show that C. heyneana contains antioxidant compounds and has potent anti-aging activity, indicating that it can be used as an anti-aging drug candidate or as a phyto-cosmeceutical. Graphical abstract: